After-effect of heavy metal pollution in a brown forest soil - Máthé-Gáspár Gabriella (Acta biologica Szegediensis, 2005)
Heavy metal pollution (of Cd-, Cr-, Zn-load: 270 kg/ha and CdSO4, K2CrO4, ZnSO4) has been shown affecting the soil actual element content, plant and soil microbial function. Pot and laboratory experiments were set up to examine the extent of pollution in the soils collected from the upper 20 cm ploughed layer in the 8th year of a long-term field trial. Actual heavy metal concentration of the polluted soils was low, although Cr and Cd values were significantly higher, exceeding the Hungarian „B” soil pollution threshold limit. Compared to control, Cd content of each plant root and shoot increased significantly, Zn and Cr content increased in few cases, Cd-Zn, Cd-Mn, and Cd-Ni interactions reflected in some instances the soil pollution, too. Microbial basal respiration rate was stimulated by Zn and Cd treatment and it inhibited by Cr. Based on these results we can demonstrate different after-effects of tested heavy metals determined by the changes of microbial C-metabolism. The after-effect of the observed heavy metal pollution influenced in all cases the metabolism of soil microbes, reactions of plants were less general, while Cd-load exhibited the most significant effect.